Bound and periodic solutions of the Riccati equation in Banach space. (1995) - Dorogovtsev, A. Ya.; Petrova, T. A.
Abstract : An abstract, nonlinear, differential equation in Banach space is considered. Conditions are presented for the existence of bounded solutions of this equation with a bounded right side, and also for the existence of stationary (periodic) solutions of this equation with a stationary (periodic) process in the right side.